Augmented Feedback Response Prediction by Peak Vertical Ground Reaction Force in Adolescent Female Athletes - Hannah Jaime; Drew Rutherford; Becky Heinert; C. Nate Vannatta; Sherwin Toribio; Thomas W Kernozek (International Journal of Sports Physical Therapy)
# Background and Purpose